2020
DOI: 10.2147/dmso.s236698
|View full text |Cite
|
Sign up to set email alerts
|

<p>Associations Between Thyroid Hormones and Glycated Albumin in Euthyroid and Subclinical Hypothyroid Individuals: Results of an Observational Study</p>

Abstract: Although overt thyroid dysfunction has been found to influence the level of glycated albumin (GA), the associations between thyroid hormones and GA in individuals with euthyroidism and subclinical hypothyroidism (SHypo) are still unknown. The present study aimed to investigate whether thyroid hormones were related to GA in euthyroid and SHypo individuals. Methods: We recruited 685 euthyroid and 103 SHypo subjects with normal weight from communities in Shanghai. Electrochemiluminescence immunoassay was used to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 32 publications
1
8
0
Order By: Relevance
“…However, contradictory findings were reported in others (17,35,36). Similar to our findings in pregnant women, several crosssectional studies among Chinese population reported that a decreased sensitivity/increased resistance to thyroid hormones were associated with reduced risk of pre-diabetes (17), lowered levels of HbA1c (35), or body mass index (BMI) (36). A crosssectional study (17) among Chinese adults reported that per SD increase in TSHI, TT4RI, and parametric TFQI and decrease in FT3/FT4 were associated with decreased risk of prediabetes by 9%-11%.…”
Section: Results Explanation and Potential Mechanisms Of Thyroid Resi...mentioning
confidence: 84%
See 1 more Smart Citation
“…However, contradictory findings were reported in others (17,35,36). Similar to our findings in pregnant women, several crosssectional studies among Chinese population reported that a decreased sensitivity/increased resistance to thyroid hormones were associated with reduced risk of pre-diabetes (17), lowered levels of HbA1c (35), or body mass index (BMI) (36). A crosssectional study (17) among Chinese adults reported that per SD increase in TSHI, TT4RI, and parametric TFQI and decrease in FT3/FT4 were associated with decreased risk of prediabetes by 9%-11%.…”
Section: Results Explanation and Potential Mechanisms Of Thyroid Resi...mentioning
confidence: 84%
“…Elevated indices of thyroid resistance has been observed to be associated with multiple unfavorable metabolic factors or disorders in general population including adipocyte fatty-acidbinding protein (34), obesity (15), type 2 diabetes, metabolic syndromes, or even diabetes-related mortality (14). However, contradictory findings were reported in others (17,35,36). Similar to our findings in pregnant women, several crosssectional studies among Chinese population reported that a decreased sensitivity/increased resistance to thyroid hormones were associated with reduced risk of pre-diabetes (17), lowered levels of HbA1c (35), or body mass index (BMI) (36).…”
Section: Results Explanation and Potential Mechanisms Of Thyroid Resi...mentioning
confidence: 99%
“…Contrary to most previous studies, our result showed decreased sensitivity to thyroid hormones has a protective effect on prediabetes, which was consistent in subgroup analyses among different age, gender, and BMI categories. A cross-sectional study in China also found a negative association between HbA 1c and TSHI, though it did not reach statistical significance ( 24 ). The contradictory results from the aforementioned studies could be attributed to differences in age, gender, ethnicity, and iodine status of study population.…”
Section: Discussionmentioning
confidence: 99%
“…Thyroid hormones can promote the decomposition of albumin and affect the level of serum GA. Hyperthyroidism may lower the values of GA, while hypothyroidism may increase the values. Even in people with normal thyroid function, GA is negatively correlated with serum free triiodothyronine and free thyroxine 43 …”
Section: Gamentioning
confidence: 96%